2015
DOI: 10.1088/0953-2048/29/1/015003
|View full text |Cite
|
Sign up to set email alerts
|

Influence of superconductor film composition on adhesion strength of coated conductors

Abstract: The effect of high temperature superconductor (HTS) film composition on the adhesion strength of rare-earth barium copper oxide coated conductors (CCs) has been studied. It has been found that the mechanical integrity of the superconductor layer is very susceptible to the defects especially those along the ab plane, probably due to the weak interfaces between the defects and the matrix. Gd and Y in the standard composition were substituted with Sm and the number of in-plane defects was drastically reduced. Con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 24 publications
0
19
0
Order By: Relevance
“…The whole construction of the CC can be regarded as a mechanical structure consisting of ceramic and metal layers attached together. As a result, the bonding strength of the CC in the transverse direction is mainly determined by the cohesive bonding strength in the matrix of each ceramic layer itself and adhesive strength between the interfaces [10].…”
Section: Introductionmentioning
confidence: 99%
“…The whole construction of the CC can be regarded as a mechanical structure consisting of ceramic and metal layers attached together. As a result, the bonding strength of the CC in the transverse direction is mainly determined by the cohesive bonding strength in the matrix of each ceramic layer itself and adhesive strength between the interfaces [10].…”
Section: Introductionmentioning
confidence: 99%
“…Once the transverse stress on the CC tape is greater than its interfacial delamination strength, severe degradation occurs irreversibly. Some testing methods have been used to investigate the delamination behaviour of REBCO CC tapes, including the anvil and pin-pull transverse tensile tests [21][22][23][24][25][26][27], peel tests [28,29], cleavage tests [30], and anvil shear tests [31]. Among them, the anvil and pin-pull transverse tensile tests are widely used to determine the transverse tensile delamination strength.…”
Section: Introductionmentioning
confidence: 99%
“…Kesgin et al used the T peel test to delaminate CC samples, and the delamination force and surface topography were measured. It was concluded that the delamination could occur between the HTS layer and buffer layer or inside the HTS layer [15].…”
mentioning
confidence: 99%
“…First, the direct delamination by peeling force could cause micro-cracks in the YBCO layer, which might be caused by the local curve which exceeded the radius limitation of CC [19]. Second, the YBCO layer near the edges was difficult to delaminate, because the adhesion strength was larger there [15]. Therefore, the delamination operation was conducted at room temperature as following: Both edges of the original sample were sheared, with the CC width decreasing to 3.63 mm; The sheared sample were placed in liquid nitrogen, and could delaminate by itself, similar to the report of Takematsu et al [7].…”
mentioning
confidence: 99%